Pedagogical Work In the Modern School and Antisocial Behavior of Students - Msc. Sanja Gacov (International Journal of Sciences: Basic and Applied Research (IJSBAR), 2023)
In the school system in the countries, in addition to the teaching staff, the schools also employ professional collaborators - pedagogues whose main task is to provide professional help and support to the participants in the work in the schools in order to be successful in the realization of school education and the effects that have been achieved to be better. Their professional goal is aimed at encouraging development and in identifying and understanding the difficulties students face and providing assistance in overcoming them, as well as preventing learning and behavioral difficulties. In addition, their professional role is realized through joint work with the teachers and the management of the school in order to ensure optimal conditions for learning and development of the students and the successful functioning of the school as an institution. They also provide support to parents and answer questions important to their children’s development and education. In modern conditions, we have to talk about the presence of many requests to which the school must respond. The real clients of the school are the student, his family, employers, society, professional elites, while maintaining a certain position of the state. For the educational system, this means that state educational institutions are obliged, on the one hand, to conduct a dialogue with all consumers of education (the goal is to find a reasonable compromise), and on the other hand, to constantly create, update and multiply the range of educational services, whose quality and effectiveness will be determined by the consumer. Otherwise, the public school cannot fully fulfill its functions. It is no longer enough for a modern school to provide a graduate pedagogue with knowledge for decades to come. In the labor market and from the point of view of life prospects, the ability and willingness to learn and retrain all their lives are becoming more and more demanded. And for this, obviously, it is necessary to learn differently, in different ways. The concept, system and organization of pedagogical work in schools are closely related and conditioned by the functioning of a complete pedagogical and psychological service as an integral part of the educational process. After all, a solid and correct pedagogical, psychological and diagnosis with a prognosis for the development and subsequent therapy for the social-educational behavior of the student can only be given by an expert team. The advancement of the pedagogical work in the school, for which a new scientific discipline of pedagogical sociology has been established, is one of the basic tasks in the realization of this role. We should understand it as a complex of a multitude of actors that influence the development and establishment of the disturbed psycho-bio-socio balance. The problem of this research is the successful realization of the pedagogical work in the school. In this context, the pedagogical work in the school should be seen in solving the pedagogical problems that are within its competence. One of the tasks of pedagogical work is social and professional influence among children to achieve a change in behavior in a positive direction, i.e. correcting the deviant, disturbed, antisocial behavior of the person who deviates from what is acceptable for social norms. There are a large number of situations where students show this kind of behavior, that is, behavior that we can define as deviant, antisocial, antisocial, etc. and thus the student’s behavior can be treated as a social or pedagogical problem. A pedagogical problem is, for example, the student’s escape from school. There must be a reason for running away, and it needs to be discovered. Working with such children leads to the realization that the student runs away in order to avoid undesirable situations in the classroom, where he feels belittled, embarrassed, underestimated. Either he runs away, because he is not given enough attention, is neglected, the students and the teacher make fun of him, he feels inferior, insulted, or he runs away because he is not adapted to the social environment. This and a series of other moments are only part of the pedagogical problems that require resolution. The degree and ability to solve problems from a pedagogical aspect will depend on the extent to which we contribute to such children being able to fit more painlessly into school life and the social environment in the future. After all, the function of the educational process is education, adaptation and training of young people for life in social conditions. With our research, we will contribute to an easier and more successful clarification of the problems that arise as a result of the antisocial behavior of students, and thus we will help in their successful resolution by applying various educational measures and also influence the improvement of the preventive actions of educators and professional services in primary school. From a methodological point of view, it will be a small, modern empirical research.